PENGARUH DISPLAY PRODUK, SERVICE QUALITY, DAN PRICE DISCOUNT TERHADAP PURCHASE DECISION DENGAN LOYALITY SEBAGAI VARIABEL INTERVENING PADA YO WES MIE DI JALAN CEMPAKA SITUBONDO - Deigo Oktaviano; Riska Ayu Pramesthi; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the Effect of Product Display, Service Quality, and Price Discount on Purchase Decision with Loyalty as an Intervening Variable at Yo Wes Mie on Jalan Cempaka Situbondo. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The test results show that Product Display has a positive and significant effect on Loyalty, Service Quality has a positive but not significant effect on Loyalty, Price Discount has a positive and significant effect on Loyalty, Product Display has a negative but significant effect on Purchase Decision, Service Quality has a positive but not significant effect on Purchase Decision, Price Discount has a positive and significant effect on Loyalty, Loyalty has a positive and significant effect on Purchase Decision, Product Display has a positive and significant effect on Purchase Decision through Loyalty, Service Quality has a positive but not significant effect on Purchase Decision through Loyalty, Price Discount has a positive and significant effect on Purchase Decision through Loyalty